Time-frequency responses of generalized first order parametric sections* - Piwowar Anna (Archives of Electrical Engineering, 2015)
This paper presents the method of analysis of parametric systems in frequency domain. These systems are also referred to as linear time varying systems (LTV). The article includes a description of an analytical method for determining the frequency response of the first order parametric circuit with non-periodically variable parameters. The results have been illustrated by an example.